A novel protein FNDC3B-267aa encoded by circ0003692 inhibits gastric cancer metastasis via promoting proteasomal degradation of c-Myc - Liu, Yu-Ying; Zhang, Yu-Ying; Ran, Ling-Yu; Huang, Bo; Ren, Jun-Wu; Ma, Qiang; Pan, Xiao-Juan; Yang, Fei-Fei; Liang, Ce; Wang, Xiao-Lin; Wang, Shi-Min; Ran, Ai; et al. (Journal of translational medicine, 2024)
Gastric cancer (GC) ranks fifth in global cancer incidence and third in mortality rate among all cancer types. Circular RNAs (circRNAs) have been extensively demonstrated to regulate multiple malignant biological behaviors in GC. Emerging evidence suggests that several circRNAs derived from FNDC3B play pivotal roles in cancer. However, the role of circFNDC3B in GC remains elusive. We initially screened circFNDC3B with translation potential via bioinformatics algorithm prediction. Subsequently, Sanger sequencing, qRT-PCR, RNase R, RNA-FISH and nuclear-cytoplasmic fractionation assays were explored to assess the identification and localization of circ0003692, a circRNA derived from FNDC3B. qRT-PCR and ISH were performed to quantify expression of circ0003692 in human GC tissues and adjacent normal tissues. The protein-encoding ability of circ0003692 was investigated through dual-luciferase reporter assay and LC/MS. The biological behavior of circ0003692 in GC was confirmed via in vivo and in vitro experiments. Additionally, Co-IP and rescue experiments were performed to elucidate the interaction between the encoded protein and c-Myc. We found that circ0003692 was significantly downregulated in GC tissues. Circ0003692 had the potential to encode a novel protein FNDC3B-267aa, which was downregulated in GC cells. We verified that FNDC3B-267aa, rather than circ0003692, inhibited GC migration in vitro and in vivo. Mechanistically, FNDC3B-267aa directly interacted with c-Myc and promoted proteasomal degradation of c-Myc, resulting in the downregulation of c-Myc-Snail/Slug axis. Our study revealed that the novel protein FNDC3B-267aa encoded by circ0003692 suppressed GC metastasis through binding to c-Myc and enhancing proteasome-mediated degradation of c-Myc. The study offers the potential applications of circ0003692 or FNDC3B-267aa as therapeutic targets for GC.